2022
DOI: 10.3390/acoustics4030048
|View full text |Cite
|
Sign up to set email alerts
|

The Acoustics of the Palace of Charles V as a Cultural Heritage Concert Hall

Abstract: This paper analyses the acoustic behaviour of the Palace of Charles V from a room acoustics perspective but also ponders the uniqueness of the space and its ability to engage and enhance the audience experience. The Palace of Charles V is a relevant part of the historical heritage of Granada. It has an architectural but also an acoustic uniqueness that deserves research. A measurement campaign was made to calculate parameters such as T30, IACC, C80 or Gm, and to explain the behaviour of the Palace. The BQI is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…A previous review of the literature 1 identified twenty-eight studies related to acoustic measurements from various locations around the world between 2016–2022. Twenty of them were conducted in Europe 2 21 , four of them in Asia 22 – 25 , three of them in America 26 28 , and the remaining one in Africa 29 . This indicates that only three of the studies were conducted in the Americas, and none of them focused on the Mayan culture, despite its significant role in the development of the inhabitants in America.…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…A previous review of the literature 1 identified twenty-eight studies related to acoustic measurements from various locations around the world between 2016–2022. Twenty of them were conducted in Europe 2 21 , four of them in Asia 22 – 25 , three of them in America 26 28 , and the remaining one in Africa 29 . This indicates that only three of the studies were conducted in the Americas, and none of them focused on the Mayan culture, despite its significant role in the development of the inhabitants in America.…”
Section: Background and Summarymentioning
confidence: 99%
“…To read and analyze this data, it is recommended to use Matlab software. Additionally, acoustic parameters can be obtained from this data using the Aurora tool for Audacity, which has been used in previous works 6 , 8 , 17 , 21 , 22 .…”
Section: Usage Notesmentioning
confidence: 99%